2021
DOI: 10.1101/2021.06.27.450102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Release of endogenous dynorphin opioids in the prefrontal cortex disrupts cognition

Abstract: Following repeated opioid use, some dependent individuals experience persistent cognitive deficits that contribute to relapse of drug-taking behaviors, and one component of this response may be mediated by the endogenous dynorphin/kappa opioid system in neocortex. In mice, we find that acute morphine withdrawal evokes dynorphin release in the medial prefrontal cortex (PFC) and disrupts cognitive function by activation of local kappa opioid receptors (KORs). Immunohistochemical analyses using a phospho-KOR anti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…aCSF = artificial cerebrospinal fluid; DNMST = delayed nonmatchingto-sample task; IEV = intermittent ethanol vapor; KOR = kappaopioid receptor; mPFC = medial prefrontal cortex; nor-BNI = norbinaltorphimine (Figure3B) and indicative of a canonical mPFC KOR agonist-mediated reduction in working memory performance. These results correspond well with data suggesting that mPFC KOR presynaptic and postsynaptic mechanisms contribute to development of KOR agonist-mediated conditioned place aversions14 and deficits in a delayed alternation task,50 although both of these previous studies utilized systemic KOR agonist injections in conjunction with mPFC nor-BNI infusions whereas the current experiment utilized site-specific mPFC infusions of both the KOR agonist and antagonist. The present results demonstrate mPFC KOR-mediated regulation of working memory and support the hypothesis that alcohol dependence-induced dysregulation of mPFC KOR function could contribute to working memory impairment.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…aCSF = artificial cerebrospinal fluid; DNMST = delayed nonmatchingto-sample task; IEV = intermittent ethanol vapor; KOR = kappaopioid receptor; mPFC = medial prefrontal cortex; nor-BNI = norbinaltorphimine (Figure3B) and indicative of a canonical mPFC KOR agonist-mediated reduction in working memory performance. These results correspond well with data suggesting that mPFC KOR presynaptic and postsynaptic mechanisms contribute to development of KOR agonist-mediated conditioned place aversions14 and deficits in a delayed alternation task,50 although both of these previous studies utilized systemic KOR agonist injections in conjunction with mPFC nor-BNI infusions whereas the current experiment utilized site-specific mPFC infusions of both the KOR agonist and antagonist. The present results demonstrate mPFC KOR-mediated regulation of working memory and support the hypothesis that alcohol dependence-induced dysregulation of mPFC KOR function could contribute to working memory impairment.…”
supporting
confidence: 89%
“…The present experiment evaluated working memory performance in the DNMST following long‐term IEV during spontaneous withdrawal when BECs had dropped to negligible levels (see Figure 1A) following the daily ethanol vapor exposure. Recent data evaluating DYN/KOR contributions to a mPFC‐dependent delayed alternation task 50 showed that naloxone‐precipitated morphine withdrawal induced deficits that appeared to be blunted by local nor‐BNI administration. However, the presence of naloxone to induce a withdrawal response in conjunction with nor‐BNI could complicate the interpretation of those results, as could the short morphine regimen utilized (i.e., 4 days) to induce deficits compared with the long‐term IEV exposure of the current experiment (i.e., 4 months).…”
Section: Discussionmentioning
confidence: 99%
“…Along with other sensors of opioid signaling 11,32 , this study establishes the first genetically encoded fluorescent protein biosensor for an opioid drug, enabling real-time quantification. Furthermore, the enantioselectivity encourages biosensor development to investigate “chiral switching” of other drugs where a single enantiomer substitutes a clinically used racemate 33 .…”
mentioning
confidence: 99%
“…The Kennedy laboratory is making headway in analytical techniques to allow rapid measurements of dynorphin using microdialysis and liquid chromatography/mass spectrometry, but these methods are not currently widely available ( Li et al, 2009 , Zhou et al, 2013 , Al-Hasani et al, 2018 ). The Chavkin laboratory has recently used the sensor kLight1.2a to detect both pharmacological and endogenously released KOR ligands in mice ( Abraham et al, 2021 ), which would be useful to determine if there is upregulation of DYN after cocaine self-administration. Though several KOR antibodies have been created, they may lack specificity, as is often the case with antibodies against G-protein coupled receptors (for review, see Michel et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%